1998
DOI: 10.1038/sj.sc.3100684
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysreflexia during urodynamics

Abstract: Autonomic dysre¯exia (AD) is an acute syndrome characterised by inappropriate and massive autonomic response that occurs in patients with spinal cord injury above the T6 level. Aims: to evaluate the incidence of AD during cystometry and the relationships with clinical and urodynamic features. Patients and methods: Forty-eight spinal cord injury patients were studied by neurological and urological examination and urodynamic evaluation with concurrent recording of blood pressure, heart rate and symptoms and sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 15 publications
5
63
3
Order By: Relevance
“…Moreover, two of these studies mentioned that some patients in the group that they defined as normotensive showed AD symptoms. 6,9 No one in the non-AD group in the present study had any AD symptoms. Both this study and the previous report by Linsenmeyer et al 6 reveal that the absolute levels of BP is not crucial to symptomatic presentation.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Moreover, two of these studies mentioned that some patients in the group that they defined as normotensive showed AD symptoms. 6,9 No one in the non-AD group in the present study had any AD symptoms. Both this study and the previous report by Linsenmeyer et al 6 reveal that the absolute levels of BP is not crucial to symptomatic presentation.…”
Section: Discussionmentioning
confidence: 58%
“…This percentage of silent AD is higher than three previous studies that reported 35, 38 and 43% respectively. 6,8,9 This discrepancy may be due to the different criteria of AD in these studies. Two of them used definite levels of SBP/DBP values as 160/100 and 150/100 mmHg, respectively, whereas one used an SBP increment percentage of 30% of baseline value.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…A number of studies examined the AD reaction during urodynamic evaluation 9,10 and actual bowel program. 11,12 Our group previously investigated the AD responses before, during and after a bowel program involving manual removal of stool in lateral recumbency in patients with cervical SCI.…”
Section: Introductionmentioning
confidence: 99%